Unveiling Yield Potential in Pakistani Bread Wheat Through Genotype x Environment Interactions - Ullah, Rafi; Khan, Fahim Ullah; Ullah, Inam (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2025)
This research investigates the interplay of genotypes and year on yield and related traits in bread wheat. Two hundred wheat genotypes, including commercial varieties and landraces were evaluated at Hazara University, Pakistan during 2020-2021 and 2021-2022 crop seasons. Analysis of variance revealed significant differences among genotypes, years, and genotype × year interactions (G × Y) for traits like tillers per square meter, grain weight per spike, grains per spike, 1000-grain weight, biological yield, and grain yield. Descriptive statistics outlined the range and mean values for these traits over two years. Noteworthy genotypes, such as Milat-2011 (maximum tillers), Khirman (heaviest grain weight per spike), NIFA-Aman (most grains per spike), and Pakistan-13 (heaviest 1000-grain weight), showed superior performance. Tandojam-83 led in biological yield, and Punjab-1 excelled in grain yield. Principal Component Analysis (PCA) identified biological yield and grain yield as major contributors to genetic variation. Cluster analysis revealed significant variability, grouping genotypes like Punjab-1, Tandojam-83, Punjab-96, Ufaq, and others into distinct clusters. Significant positive correlations were found between tillers per square meter with both biological yield and grain yield. This study offers valuable insights into G × Y interactions and genetic diversity, aiding wheat breeding programs aimed at improving yield and stability.